Plasma treatment: An alternative and sustainable green approach for decontamination of mycotoxin in dried food products - Rajeev Ranjan; Arun Kumar Gupta; R. Pandiselvam; Anil Kumar Chauhan; Saamir Akhtar; Avinash Kumar Jha; Pratiksha; Tabli Ghosh; Soumya Ranjan Purohit; Muzamil Ahmad Rather; Dhan Prakash; Rajesh Singh; et al. (Journal of Agriculture and Food Research, 2023)
In the realm of food safety, dried foods have traditionally been perceived as having a lower risk profile. However, recent reports have highlighted concerning levels of mycotoxin contamination in dried food products, such as dried fruits, vegetables, and spices, exceeding permissible limits. This contamination not only compromises shelf life but also poses a significant threat to consumers, while depleting the bioactive components of these products. The food industry grapples with considerable challenges arising from the substantial risk of mycotoxin contamination in dried foods. To meet the demands of a disc; erning food market, there is an imperative need for sustainable mycotoxin-degrading technologies. These technologies must be non-thermal and chemical-free, minimizing thermal damage to treated food to preserve essential nutrients, ultimately enhancing food quality and safety. Developing non-thermal decontamination technologies for dried foods holds enormous economic and public health significance.This review centers its focus on the decontamination of dried foods, proposing a green approach through the utilization of Cold Plasma Technology (CPT). We delve into the working principles and applications of CPT in dried foods, highlight the influential factors affecting its efficacy, and acknowledge the limitations of this innovative technique. Furthermore, we pinpoint and explore emerging research opportunities in the decontamination of dried foods, particularly in conjunction with other complementary methods. CPT, an evolving and environmentally friendly technology, exhibits promising capabilities in controlling pathogens in dried food products and extending their shelf life. Critical determinants encompass the parameters of cold plasma, operational conditions, food-related variables, and microbiological factors, which collectively influence the efficacy of CPT. We advocate for future research dedicated to assessing the impact of CPT on various mycotoxins, food composition, and its interaction with food-related factors. In this vein, it is imperative to emphasize the scaling up of this technology for practical commercial applications, addressing the growing need for enhanced food safety in dried products.